The effect of the principle of the best interests of the child based on the presumption pater is est - Rivera, Karen (2018)
This article seeks to demonstrate that the presumption pater is est partially and negatively affects the principle of the best interest of the child as of the Cassation No. 2726-2012-DEL SANTA. In this way, it seeks to analyze the rights that encompass this principle and, with it, propose as a solution the modifications that regulate the mentioned presumption, without needing to propose a derogation from it.